Carrier for improving conductive heating performance of carbon nanotubes and preparation method thereof

By adopting a three-layer structure of modified nanoalumina/water-soluble polymer resin carrier layer and carbon nanotube layer in the heating element, the problem of low thermal efficiency of existing heating elements is solved, and the conductive heating performance of carbon nanotubes is improved and Connection strength achieves more efficient thermal conductivity and stability.

CN119119553AInactive Publication Date: 2024-12-13YISHIWEN BIOTECHNOLOGY (TIANJIN) CO LTD +1

Patent Information

Application Number
CN202411604539.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing heating elements have low thermal efficiency, low power density, uneven thermal distribution and low safety. In practical applications, the conductive heating efficiency of carbon nanotube conductive films is affected by the addition of dispersants and binders.

Method used

Adopting a three-layer structure including a substrate layer, a modified nano-alumina/water-soluble polymer resin carrier layer and a carbon nanotube layer, the graft group adsorbs a dispersant on the surface of alumina to promote the compactness of carbon nanotubes. The crosslinked structure is formed and the connection between the carbon nanotubes and the substrate is enhanced by the porous structure of the alumina.

Benefits of technology

The conductive heating performance of carbon nanotubes and the binding fastness to the substrate are improved, the influence of dispersants on conductive heating is reduced, and more efficient thermal conductivity and stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119553A_ABST
    Figure CN119119553A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive heating materials, and discloses a carrier for improving the conductive heating performance of carbon nanotubes and a preparation method thereof.The carrier comprises a base material layer, a modified nanometer aluminum oxide / water-soluble polymer resin carrier layer and a carbon nanotube layer; the modified nano aluminum oxide / water-soluble polymer resin carrier layer comprises modified aluminum oxide; one or more modified groups of gamma-aminopropyltriethoxysilane, gamma-glycidyl ether oxypropyltrimethoxysilane, gamma-methacryloxypropyltrimethoxysilane, ammonium polyacrylate, sodium vinyl sulfonate, aminobenzoic acid and diallyldimethylammonium chloride are grafted on the surface of the modified aluminum oxide, and one or more modified groups of the gamma-aminopropyltriethoxysilane, the gamma-glycidyl ether oxypropyltrimethoxysilane, the gamma-methacryloxypropyltrimethoxysilane, the ammonium polyacrylate, the sodium vinyl sulfonate, the aminobenzoic acid and the diallyldimethylammonium chloride are grafted on the surface of the modified aluminum oxide. The modified nano aluminum oxide / water-soluble polymer resin carrier layer further comprises a dispersing agent; the dispersing agent is adsorbed into the modified aluminum oxide. The material obtained in the invention has good conductive heating capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive heating materials, and in particular to a carrier for improving the conductive heating performance of carbon nanotubes and a preparation method thereof. Background Art

[0002] With the rapid development of wearable devices and flexible electronic devices, the demand for flexible heating elements is increasing. Existing heating elements are mostly made of resistive heating materials such as metal wire or carbon fiber, which have problems such as low thermal efficiency, low power density, uneven heat distribution, and low safety.

[0003] The carbon nanotube conductive film exhibits a novel heating mechanism, which is different from the heating mode of traditional resistive heaters. Traditional heaters first heat up themselves and then transfer heat through temperature difference radiation and heat conduction. When the carbon nanotube film is energized, the CC covalent bonds of the carbon nanotubes are excited and oscillate. The energy generated by the oscillation radiates outward in the form of phonons, emitting far-infrared electromagnetic waves with a wavelength of 3μm-20μm. The far-infrared waves can radiate directly outward through the transparent substrate without causing energy loss due to phonon scattering. The phonon energy is transmitted in the form of far-infrared, allowing external objects to quickly absorb and heat up, realizing a new heating mechanism in which the film heats up when powered on and cools down when powered off.

[0004] In practical applications, in order to achieve the dispersion of carbon nanotubes in carbon nanotube conductive films and stable connection with other materials, dispersants are added to prevent carbon nanotubes from agglomerating; binders are added to promote the stable connection between the carbon nanotube layer and the substrate. However, the added dispersants and binders affect the conductivity and heating efficiency of carbon nanotubes. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a carrier for improving the electrical conductivity and heat generation performance of carbon nanotubes and a preparation method thereof. The material obtained in the present invention has good electrical conductivity and heat generation capabilities.

[0006] The present invention provides a carrier for improving the conductive and heating performance of carbon nanotubes, the carrier comprising a substrate layer, a modified nano-alumina / water-soluble polymer resin carrier layer and a carbon nanotube layer; The modified nano-alumina / water-soluble polymer resin carrier layer is disposed on the substrate layer, and the carbon nanotube layer is disposed on the modified nano-alumina / water-soluble polymer resin carrier layer; The modified nano-alumina / water-soluble polymer resin carrier layer comprises modified alumina, and the surface of the modified alumina is grafted with one or more modifying groups selected from γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, ammonium polyacrylate, sodium vinyl sulfonate, aminobenzoic acid, and diallyldimethylammonium chloride; The modified nano-alumina / water-soluble polymer resin carrier layer also includes a dispersant; the dispersant is adsorbed inside the modified alumina.

[0007] Furthermore, the modified nano-alumina / water-soluble polymer resin carrier layer also includes a water-soluble polymer resin.

[0008] Furthermore, the water-soluble polymer resin includes one or more of polyvinyl pyrrolidone, hydroxypropyl cellulose, acrylic resin, and polyvinyl alcohol.

[0009] Furthermore, the dispersant includes one or more of dodecylbenzenesulfonic acid and hexadecyltrimethylammonium chloride.

[0010] Furthermore, the carbon nanotube layer includes one-dimensional carbon nanomaterials.

[0011] Furthermore, the one-dimensional carbon nanomaterial includes one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0012] Furthermore, the substrate layer includes a coatable substrate.

[0013] Furthermore, the coatable substrate includes one of polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), and polyvinyl chloride (PVC).

[0014] Furthermore, the particle size of the modified alumina is 30nm-130nm.

[0015] Furthermore, the thickness of the substrate layer is 0.02 mm-0.15 mm.

[0016] Furthermore, the thickness of the modified nano-alumina / water-soluble polymer resin carrier layer is 10 μm-50 μm.

[0017] Furthermore, the thickness of the carbon nanotube layer is 0.15 μm-4.5 μm.

[0018] The present invention also provides a method for preparing the carrier for improving the conductive and heat-generating performance of carbon nanotubes, the method comprising: S1: dispersing the one-dimensional carbon nanomaterial in a solution, adding a dispersant, and mixing evenly to obtain a carbon nanotube layer slurry; S2: adjusting the pH value of the modified alumina slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a modified nano-alumina / water-soluble polymer resin carrier layer slurry; S3: coating the modified nano-alumina / water-soluble polymer resin carrier layer slurry on the surface of the coatable substrate, drying it, coating the carbon nanotube layer slurry on the modified nano-alumina / water-soluble polymer resin carrier layer, and drying it.

[0019] Furthermore, the added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanomaterial.

[0020] Furthermore, the mass concentration of the one-dimensional carbon nanomaterial in the solution is 0.5%-1.5%.

[0021] Furthermore, the solution is deionized water.

[0022] Furthermore, the specific method for adjusting the pH value of the modified alumina slurry to 2.5-3.5 is to use a glacial acetic acid solution with a mass concentration of 10%.

[0023] Furthermore, the preparation method of the glacial acetic acid solution includes mixing glacial acetic acid with deionized water.

[0024] Furthermore, the leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant.

[0025] Furthermore, the organosilicon surfactant includes BYK348.

[0026] Furthermore, the fluorine ion surfactant includes FS-3100.

[0027] Furthermore, the curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate.

[0028] Furthermore, the added amount of the leveling agent is 0.1%-2.5% of the total mass of the modified nano-alumina / water-soluble polymer resin carrier layer slurry.

[0029] Furthermore, the added amount of the curing agent is 2%-3% of the mass of the water-soluble polymer resin in the water-soluble polymer resin solution.

[0030] Furthermore, the mass ratio of the modified alumina slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-15:1.

[0031] Furthermore, the mass concentration of the water-soluble polymer resin solution is 5%-15%.

[0032] Furthermore, the preparation method of the water-soluble polymer resin solution is a conventional method, that is, dissolving and dispersing the water-soluble polymer resin in a solvent. Those skilled in the art should understand that due to the characteristics of the water-soluble polymer resin itself, different solvents are used for dissolution, for example, water, ethanol, etc. Those skilled in the art can select the solvent they need according to the water-soluble polymer resin.

[0033] Furthermore, the drying temperature is 50°C-60°C, and the drying time is 25min-35min.

[0034] Furthermore, the preparation method of the modified alumina slurry comprises: adding the modifying group to a solution containing alumina, mixing evenly, performing an aging treatment, and cooling to obtain the modified alumina slurry.

[0035] Furthermore, the ratio of the modified group to aluminum oxide is 3-6:100 by mass.

[0036] Furthermore, the method for preparing the solution containing aluminum oxide includes mixing aluminum oxide with deionized water, wherein the ratio of aluminum oxide to deionized water is 1:4 by mass.

[0037] Furthermore, there are many ways to achieve uniform mixing. In the present invention, as an example, a high shear disperser can be used for shearing treatment at 8000 rpm for 60 minutes.

[0038] Furthermore, the specific method of the aging treatment is: treating at 70°C-90°C for 230min-250min.

[0039] Furthermore, stirring may be performed during the aging process.

[0040] Furthermore, the present invention also provides the use of the carrier for improving the conductive and heating performance of carbon nanotubes in physical therapy electrodes, wearable heating clothing, wall heating paintings, and glass defrosting films.

[0041] The embodiments of the present invention have the following technical effects: 1. In the present invention, the grafted groups on the modified alumina in the modified nano alumina / water-soluble polymer resin carrier layer can promote the diffusion of the dispersant in the carbon nanotube layer into the modified alumina, thereby promoting the carbon nanotubes to form a denser and purer cross-linked structure, thereby improving the conductive and heat-generating performance of the carbon nanotubes; and the porous structure of the alumina can adsorb the carbon nanotube layer and the substrate through capillary action, and the two-way connection performance improves the bonding strength of the carbon nanotubes and the substrate, thereby improving the connection strength between the carbon nanotube layer and the substrate layer and the modified nano alumina / water-soluble polymer resin carrier layer, and the positive charge on the surface of the alumina has an attachment and fixing effect on the negatively charged carbon nanotubes. In addition, through the grafted groups on the surface of the alumina, the agglomeration of the alumina nanoparticles can be reduced, and the uniformity of the nanoparticles in the polymer resin is increased, which is conducive to obtaining a uniform modified nano alumina / water-soluble polymer resin carrier layer slurry.

[0042] 2. In the present invention, in order to further enhance the adsorption effect of the modified alumina in the modified nano-alumina / water-soluble polymer resin carrier layer on the dispersant, grafts that can cooperate with different dispersants are designed on the surface of the alumina; and the amount of grafting on the surface of the alumina is further selected to enhance the adsorption capacity of the alumina for the dispersant while preventing the grafts from being entangled with each other. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 It is a structural schematic diagram provided by Example 1 of the present invention.

[0045] The above drawings include the following reference numerals: 001-substrate layer; 101-modified nano-alumina / water-soluble polymer resin carrier layer; 201-carbon nanotube layer. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0047] In a first aspect, some embodiments of the present invention provide a carrier for improving the conductive and heat-generating performance of carbon nanotubes, the carrier comprising a substrate layer, a modified nano-alumina / water-soluble polymer resin carrier layer and a carbon nanotube layer; The modified nano-alumina / water-soluble polymer resin carrier layer is disposed on the substrate layer, and the carbon nanotube layer is disposed on the modified nano-alumina / water-soluble polymer resin carrier layer; The modified nano-alumina / water-soluble polymer resin carrier layer comprises modified alumina, and the surface of the modified alumina is grafted with one or more modifying groups selected from γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, ammonium polyacrylate, sodium vinyl sulfonate, aminobenzoic acid, and diallyldimethylammonium chloride; The modified nano-alumina / water-soluble polymer resin carrier layer also includes a dispersant; the dispersant is adsorbed inside the modified alumina.

[0048] In some embodiments, the modified nano-alumina / water-soluble polymer resin carrier layer also includes a water-soluble polymer resin.

[0049] In some embodiments, the water-soluble polymer resin includes one or more of polyvinyl pyrrolidone, hydroxypropyl cellulose, acrylic resin, and polyvinyl alcohol.

[0050] In some embodiments, the dispersant includes one or more of dodecylbenzenesulfonic acid and hexadecyltrimethylammonium chloride.

[0051] In some embodiments, the carbon nanotube layer includes one-dimensional carbon nanomaterials.

[0052] In some embodiments, the one-dimensional carbon nanomaterial includes one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0053] In some embodiments, the substrate layer comprises a coatable substrate.

[0054] In some embodiments, the coatable substrate includes one of polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), and polyvinyl chloride (PVC).

[0055] In some embodiments, the particle size of the modified alumina is 30nm-130nm.

[0056] In some embodiments, the thickness of the substrate layer is 0.02 mm-0.15 mm.

[0057] In some embodiments, the thickness of the modified nano-alumina / water-soluble polymer resin carrier layer is 10 μm-50 μm.

[0058] In some embodiments, the carbon nanotube layer has a thickness of 0.15 μm-4.5 μm.

[0059] In a second aspect, some embodiments of the present invention further provide a method for preparing a carrier for improving the conductive and heat-generating performance of carbon nanotubes, the method comprising: S1: dispersing the one-dimensional carbon nanomaterial in a solution, adding a dispersant, and mixing evenly to obtain a carbon nanotube layer slurry; S2: adjusting the pH value of the modified alumina slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a modified nano-alumina / water-soluble polymer resin carrier layer slurry; S3: coating the modified nano-alumina / water-soluble polymer resin carrier layer slurry on the surface of the coatable substrate, drying it, coating the carbon nanotube layer slurry on the modified nano-alumina / water-soluble polymer resin carrier layer, and drying it.

[0060] In the method of the present invention, after the carbon nanotube layer slurry is coated on the modified nano-alumina / water-soluble polymer resin carrier layer, a drying treatment is performed, and the dispersant in the carbon nanotube layer slurry is adsorbed inside the modified alumina by the modified nano-alumina / water-soluble polymer resin carrier layer.

[0061] In some embodiments, the added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanomaterial.

[0062] In some embodiments, the mass concentration of the one-dimensional carbon nanomaterial in the solution is 0.5%-1.5%.

[0063] In some embodiments, the solution is deionized water.

[0064] In some embodiments, the specific method for adjusting the pH value of the modified alumina slurry to 2.5-3.5 is: using a glacial acetic acid solution with a mass concentration of 10%.

[0065] In some embodiments, the method for preparing the glacial acetic acid solution includes mixing glacial acetic acid with deionized water.

[0066] In some embodiments, the leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant.

[0067] In some embodiments, the organosilicon surfactant includes BYK348.

[0068] In some embodiments, the fluoride ion surfactant includes FS-3100.

[0069] In some embodiments, the curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate.

[0070] In some embodiments, the added amount of the leveling agent is 0.1%-2.5% of the total mass of the modified nano-alumina / water-soluble polymer resin carrier layer slurry.

[0071] In some embodiments, the curing agent is added in an amount of 2%-3% of the mass of the water-soluble polymer resin in the water-soluble polymer resin solution.

[0072] In some embodiments, the ratio of the modified alumina slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-15:1 by mass.

[0073] In some embodiments, the mass concentration of the water-soluble polymer resin solution is 5%-15%.

[0074] In some embodiments, the drying temperature is 50° C.-60° C., and the drying time is 25 min-35 min.

[0075] In some embodiments, the method for preparing the modified alumina slurry includes: adding a modifying group to a solution containing alumina, mixing evenly, performing an aging treatment, and cooling to obtain the modified alumina slurry.

[0076] In the process of modifying aluminum oxide in the present invention, the modifying groups react with the hydroxyl groups on the surface of the aluminum oxide to undergo condensation, thereby achieving the grafting of the modifying groups on the surface of the aluminum oxide, thereby completing the modification process.

[0077] In some embodiments, the ratio of the modifying group to aluminum oxide is 3-6:100 by mass.

[0078] In some embodiments, the method for preparing the solution containing aluminum oxide includes mixing aluminum oxide with deionized water, wherein the ratio of aluminum oxide to deionized water is 1:4 by mass.

[0079] In some embodiments, there are multiple ways to achieve uniform mixing. In the present invention, as an example, a high shear disperser can be used to perform shearing treatment at 8000 rpm for 60 minutes.

[0080] In some embodiments, the specific method of the aging treatment is: treating at 70° C.-90° C. for 230 min-250 min.

[0081] In some embodiments, stirring may be performed during the aging process.

[0082] A comparative analysis is performed below in conjunction with specific embodiments and comparative examples.

[0083] Example 1

[0084] (1) Modified nano-alumina / water-soluble polymer resin carrier layer: Preparation of modified alumina slurry: by mass, alumina and deionized water = 1:4, add γ-aminopropyltriethoxysilane; by mass, γ-aminopropyltriethoxysilane and alumina = 3:100, high shear disperser 8000 rpm shear treatment for 60 minutes, then put the above dispersion into a three-necked bottle, stir and age at 80°C for 240 minutes, and cool naturally for use; Prepare the slurry: weigh 35.3g of modified nano-alumina slurry, adjust the pH to 2.5-3.5 with 10% glacial acetic acid dilute solution, stir for half an hour until the powder is evenly dispersed and in a transparent sol state; add 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%; stir for half an hour and mix evenly; then add 1.8g of leveling agent BYK348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain modified nano-alumina / water-soluble polymer resin carrier layer slurry.

[0085] The above-mentioned liquid was coated on the PET substrate by a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes to obtain a modified nano-alumina / water-soluble polymer resin carrier layer. The tested coating thickness was 20.4 μm.

[0086] (2) Carbon nanotube layer: 8 g of multi-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzene sulfonic acid was added, the added mass of dodecylbenzene sulfonic acid was 5% of the multi-walled carbon nanotubes, and emulsified and dispersed by a high-speed emulsifier to obtain a carbon nanotube layer slurry; The carbon nanotube layer slurry was coated on the modified nano-alumina / water-soluble polymer resin carrier layer using a coating rod, and dried in a 55° C. forced air drying oven for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 0.15 μm.

[0087] Example 2

[0088] (1) Modified nano-alumina / water-soluble polymer resin carrier layer: Preparation of modified alumina slurry: by mass, alumina and deionized water are mixed at a ratio of 1:4, sodium vinyl sulfonate is added, and the mass ratio of sodium vinyl sulfonate to alumina is 3:100, and the high shear disperser is sheared at 8000 rpm for 60 minutes, and then the above dispersion is placed in a three-necked bottle, stirred and aged at 80°C for 240 minutes, and naturally cooled for use; Prepare the slurry: weigh 35.3g of modified alumina slurry, adjust the pH to 2.5-3.5 with 10% glacial acetic acid dilute solution, stir for half an hour until the powder is evenly dispersed and in a transparent sol state; add 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%; stir for half an hour and mix evenly; then add 1.8g of leveling agent BYK-348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain a modified nano alumina / water-soluble polymer resin carrier layer slurry.

[0089] The above-mentioned liquid was coated on the PET substrate with a coating rod, and placed in a 55°C forced air drying oven for drying for 30 minutes. The tested coating thickness was 10.9 μm. (2) Carbon nanotube layer: 8 g of single-walled carbon nanotubes were added to 1000 mL of deionized water, and hexadecyltrimethylammonium chloride was added as a dispersing aid, the added mass of hexadecyltrimethylammonium chloride was 5% of the single-walled carbon nanotubes, and dispersed by an ultrasonic machine to obtain a carbon nanotube layer slurry; The carbon nanotube layer slurry was coated on the modified nano-alumina / water-soluble polymer resin carrier layer using a coating rod, and dried in a 55° C. forced air drying oven for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 2.8 μm.

[0090] Example 3

[0091] (1) Modified nano-alumina / water-soluble polymer resin carrier layer: Preparation of modified alumina slurry: by mass, alumina and deionized water are mixed at a ratio of 1:4, aminobenzoic acid is added, and the mass ratio of aminobenzoic acid to alumina is 4:100, and the high shear disperser is sheared at 8000 rpm for 60 minutes, and then the above dispersion is placed in a three-necked bottle, stirred and aged at 70°C for 240 minutes, and naturally cooled for use; Prepare the slurry: weigh 35.3g of modified alumina slurry, adjust the pH to 2.5-3.5 with 10% glacial acetic acid dilute solution, stir for half an hour until the powder is evenly dispersed and in a transparent sol state; add 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%, stir for half an hour, and mix evenly; then add 1.8g of leveling agent BYK-348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain a modified nano alumina / water-soluble polymer resin carrier layer slurry.

[0092] The above-mentioned liquid was coated on the PET substrate using a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes. The tested coating thickness was 48.7 μm.

[0093] (2) Carbon nanotube layer: 8 g of single-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzenesulfonic acid dispersant was added, with the added mass of dodecylbenzenesulfonic acid being 5% of the single-walled carbon nanotubes, and dispersed by an ultrasonic machine to obtain a carbon nanotube layer slurry; The carbon nanotube layer slurry was coated on the modified nano-alumina / water-soluble polymer resin carrier layer using a coating rod, and dried in a 55° C. forced air drying oven for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 4.5 μm.

[0094] Example 4

[0095] (1) Modified nano-alumina / water-soluble polymer resin carrier layer: Preparation of modified alumina slurry: by mass, alumina and deionized water are mixed at a ratio of 1:4, diallyldimethylammonium chloride is added, the mass ratio of diallyldimethylammonium chloride to alumina is 6:100, high shear disperser is used for shearing treatment at 8000 rpm for 60 minutes, and then the above dispersion is placed in a three-necked bottle, stirred and aged at 85°C for 240 minutes, and naturally cooled for use; Prepare the slurry: weigh 35.3g of modified alumina slurry, adjust the pH to 2.5-3.5 with 10% glacial acetic acid dilute solution, stir for half an hour until the powder is evenly dispersed and in a transparent sol state; add 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%; stir for half an hour and mix evenly; then add 1.8g of leveling agent BYK-348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain a modified nano alumina / water-soluble polymer resin carrier layer slurry.

[0096] The above-mentioned liquid was coated on the PET substrate using a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes. The tested coating thickness was 9.6 μm.

[0097] (2) Carbon nanotube layer: 8 g of single-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzenesulfonic acid dispersant was added, with the added mass of dodecylbenzenesulfonic acid being 2% of the single-walled carbon nanotubes; the carbon nanotube layer slurry was obtained by dispersion using an ultrasonic machine; The obtained carbon nanotube layer slurry was coated on the modified nano-alumina / water-soluble polymer resin carrier layer using a coating wire rod, and dried in a 55° C. forced air drying oven for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 1.6 μm.

[0098] Comparative Example 1: (1) Water-soluble polymer resin carrier layer: Prepare the liquid: weigh 106g of deionized water, add 32.69g of polyvinyl alcohol PVA235, stir for half an hour, and mix evenly; then add 1.7g of leveling agent BYK-348 and 4.17g of curing agent boric acid, stir for 15 minutes, and mix evenly to obtain a water-soluble polymer resin carrier layer slurry.

[0099] The water-soluble polymer resin carrier layer slurry was coated on the PET substrate with a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes to obtain a water-soluble polymer resin carrier layer. The tested coating thickness was 9.6 μm.

[0100] (2) Carbon nanotube layer: 8 g of single-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzenesulfonic acid dispersant was added, with the added mass of dodecylbenzenesulfonic acid being 2% of the single-walled carbon nanotubes; the carbon nanotube layer slurry was obtained by dispersion using an ultrasonic machine; The carbon nanotube layer slurry was coated on the water-soluble polymer resin carrier layer using a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 1.6 μm.

[0101] Comparative Example 2: 8 g of single-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzenesulfonic acid dispersant was added, with the added mass of dodecylbenzenesulfonic acid being 2% of the single-walled carbon nanotubes; the carbon nanotube layer slurry was obtained by dispersion using an ultrasonic machine; The carbon nanotube layer slurry was coated on the PET substrate using a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 1.6 μm.

[0102] Comparative Example 3: (1) Nano-alumina / water-soluble polymer resin carrier layer: Preparation of alumina slurry: by mass, alumina and deionized water are mixed in a ratio of 1:4, and sheared at 8000 rpm in a high shear disperser for 60 minutes. The dispersion is then placed in a three-necked bottle, stirred and aged at 80°C for 240 minutes, and cooled naturally for use; Weigh 35.3g of modified nano-alumina slurry, adjust the pH to 2.5-3.5 with a dilute glacial acetic acid solution with a mass concentration of 10%, stir for half an hour until the powder is evenly dispersed and in a transparent sol state; add 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%; stir for half an hour and mix evenly; then add 1.8g of leveling agent BYK348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain a modified nano-alumina / water-soluble polymer resin carrier layer slurry.

[0103] The above-mentioned liquid was coated on the PET substrate by a coating rod, and placed in a 55° C. forced air drying oven for drying for 30 minutes to obtain a modified nano-alumina / water-soluble polymer resin carrier layer. The tested coating thickness was 20.4 μm.

[0104] (2) Carbon nanotube layer: 8 g of multi-walled carbon nanotubes were added to 1000 mL of deionized water, and dodecylbenzene sulfonic acid was added, the added mass of dodecylbenzene sulfonic acid was 5% of the multi-walled carbon nanotubes, and emulsified and dispersed by a high-speed emulsifier to obtain a carbon nanotube layer slurry; The carbon nanotube layer slurry was coated on the modified nano-alumina / water-soluble polymer resin carrier layer using a coating rod, and dried in a 55° C. forced air drying oven for 30 minutes to obtain a carbon nanotube layer. The tested coating thickness was 0.15 μm.

[0105] The embodiments and comparative examples of the present invention were tested and analyzed: (1) Adhesive strength test method: The carrier prepared by the above-mentioned embodiments and comparative examples is attached to a polyester film with a release material, the release material is peeled off, and the adhesive surface is attached to a test board; the tape is attached to the test surface (carbon tube), and the sample is rolled back and forth at a speed of 600 mm / min for 2 times, the free end of the tape is folded 180°, and the adhesive surface with a length of about 25 mm is peeled off. The free end of the tape and the test board are clamped on the upper and lower chucks of an electronic intelligent tensile testing machine respectively, so that the peeling surface and the tensile direction of the testing machine are consistent, and the peeling is continuously performed at a speed of 300 mm / min. Two groups of samples are tested, and the arithmetic mean of the peeling force is calculated and converted into peel strength in units of N / 25 mm.

[0106] (2) Thermal conductivity test method: The carrier prepared by the above scheme is cut into a 27.5 mm × 200 mm rectangular strip; the rectangular strip is closely contacted with a heat source, and the heat source temperature is fixed at T1 , use an infrared thermometer to test the temperature at 1 cm away from the heat source as T 2 . Thermal conductivity = (T 1 / T 2 )×100%, the greater the thermal conductivity, the better the surface thermal conductivity of the film.

[0107] Heating rate K test method: The carrier prepared by the above scheme is cut into a 30.0mm×50.0mm rectangular strip; it is fixed using a solid test adjustable DC regulated power supply and a 30.0mm wide electrode test fixture, and a contact thermometer is used to test the temperature value T at the center of the quick heating film 1 , use a stopwatch to time t; measure the temperature rise to temperature T within a fixed time 2 , △T=T 2 -T 1 , K=△T / t.

[0108] Results and analysis: Table 1 Test results of embodiments and comparative examples

[0109] The method of the present invention successfully obtains a carrier for improving the conductive and heating performance of carbon nanotubes. The carrier of the present invention has a three-layer structure, including a substrate layer 001, a modified nano-alumina / water-soluble polymer resin carrier layer 101 and a carbon nanotube layer 201. Figure 1 As shown. Among them, the grafted groups on the alumina in the modified nano-alumina / water-soluble polymer resin carrier layer can promote the dispersant in the carbon nanotube layer to diffuse into the modified alumina, which not only promotes the carbon nanotubes to form a denser and purer cross-linked structure, but also reduces the influence of the dispersant on the conductivity and heat generation of the carbon nanotubes, thereby improving the conductivity and heat generation performance of the carbon nanotubes; and the porous structure of the alumina can adsorb the carbon nanotube layer and the substrate through capillary action, and the two-way connection performance improves the bonding strength of the carbon nanotubes and the substrate, thereby improving the connection strength between the carbon nanotube layer and the substrate layer and the modified nano-alumina / water-soluble polymer resin carrier layer. In addition, through the grafted groups on the surface of alumina, the agglomeration of alumina nanoparticles can also be reduced, and the uniformity of nanoparticles in the polymer resin is increased, which is conducive to obtaining a uniform modified nano-alumina / water-soluble polymer resin carrier layer slurry. Therefore, the carrier obtained by the present invention has a good conductivity and heat generation efficiency, which can be verified by comparing Examples 1-4 with Comparative Examples 1-2.

[0110] By grafting different modification groups on alumina, the alumina is enabled to adsorb the dispersant in the carbon nanotube layer, thereby reducing the influence of the dispersant on the electrical conductivity and heat transfer of the carbon nanotubes in the carbon nanolayer. When the number of groups grafted on alumina is different, the modification effect on alumina will be different. When the number of grafted groups is too large, it may cause entanglement between the grafted chains, reduce the adsorption capacity, and may cause a decrease in thermal conductivity, which can be verified by comparing Examples 1-2 with Example 4; and when the number of grafted groups is small or no grafting is done, it may cause incomplete modification of alumina, which can be verified by comparing Examples 1-4 with Comparative Example 3. Therefore, when the number of grafted groups is within an appropriate range, it can not only improve the adsorption of alumina on the dispersant, but also improve its thermal conductivity.

[0111] On this basis, it should be understood by those skilled in the art that the grafted groups on the surface of alumina can enhance the adsorption effect of alumina on the dispersant, mainly due to the interaction between the grafted groups on the surface of alumina and the dispersant. Only when the grafted groups find a dispersant that can match with it, can they have a better adsorption effect, which can be verified by comparing Example 1 and Example 2. It is further found that when the selected grafted groups and the dispersant are more suitable, the amount of grafting can be further reduced to achieve a more significant effect. Example 3 and Example 4 compare and verify that when the grafted group is aminobenzoic acid, it has a good adsorption effect on dodecylbenzenesulfonic acid. On the basis of reducing the number of grafts, the conductive heating efficiency of the carrier in the present invention is further improved. Therefore, when it is further preferred that the grafting is aminobenzoic acid, the dispersant selects dodecylbenzenesulfonic acid.

[0112] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.

[0113] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A carrier for improving the conductive and heat-generating performance of carbon nanotubes, characterized in that: The carrier comprises a substrate layer, a modified nano-alumina / water-soluble polymer resin carrier layer and a carbon nanotube layer; The modified nano-alumina / water-soluble polymer resin carrier layer is disposed on the substrate layer, and the carbon nanotube layer is disposed on the modified nano-alumina / water-soluble polymer resin carrier layer; The modified nano-alumina / water-soluble polymer resin carrier layer comprises modified alumina, and the surface of the modified alumina is grafted with one or more modifying groups selected from γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, ammonium polyacrylate, sodium vinyl sulfonate, aminobenzoic acid, and diallyldimethylammonium chloride; The modified nano-alumina / water-soluble polymer resin carrier layer also includes a dispersant; the dispersant is adsorbed inside the modified alumina.

2. The carrier according to claim 1, characterized in that The modified nano-alumina / water-soluble polymer resin carrier layer also includes a water-soluble polymer resin; The dispersant includes one or more of dodecylbenzenesulfonic acid and hexadecyltrimethylammonium chloride; The carbon nanotube layer includes one-dimensional carbon nanomaterial; The substrate layer comprises a coatable substrate.

3. The carrier according to claim 1, characterized in that The thickness of the substrate layer is 0.02mm-0.15mm; The thickness of the modified nano-alumina / water-soluble polymer resin carrier layer is 10 μm-50 μm; The thickness of the carbon nanotube layer is 0.15 μm-4.5 μm.

4. The method for preparing a carrier for improving the conductive and heat-generating performance of carbon nanotubes according to any one of claims 1 to 3, characterized in that: The preparation method comprises: S1: dispersing the one-dimensional carbon nanomaterial in a solution, adding a dispersant, and mixing evenly to obtain a carbon nanotube layer slurry; S2: adjusting the pH value of the modified alumina slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a modified nano-alumina / water-soluble polymer resin carrier layer slurry; S3: coating the modified nano-alumina / water-soluble polymer resin carrier layer slurry on the surface of the coatable substrate, drying it, coating the carbon nanotube layer slurry on the modified nano-alumina / water-soluble polymer resin carrier layer, and drying it.

5. The preparation method according to claim 4, characterized in that: The added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanomaterial; The mass concentration of the one-dimensional carbon nanomaterial in the solution is 0.5%-1.5%; The leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant; The curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate; The amount of the leveling agent added is 0.1%-2.5% of the total mass of the modified nano-alumina / water-soluble polymer resin carrier layer slurry; The amount of the curing agent added is 2%-3% of the mass of the water-soluble polymer resin in the water-soluble polymer resin solution; The ratio of the modified alumina slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-15:1 by mass; The mass concentration of the water-soluble polymer resin solution is 5%-15%.

6. The preparation method according to claim 4, characterized in that: The drying temperature is 50° C.-60° C., and the drying time is 25 min-35 min.

7. The preparation method according to claim 4, characterized in that: The preparation method of the modified alumina slurry comprises: adding a modifying group into a solution containing alumina, mixing evenly, performing an aging treatment, and cooling to obtain the modified alumina slurry.

8. The preparation method according to claim 7, characterized in that: The ratio of the modified group to the aluminum oxide is 3-6:100 by mass; The method for preparing the solution containing aluminum oxide includes mixing aluminum oxide with deionized water, wherein the ratio of aluminum oxide to deionized water is 1:4 by mass.

9. The preparation method according to claim 7, characterized in that: The specific method of the aging treatment is: treating at 70°C-90°C for 230min-250min.

10. Use of the carrier for improving the conductive and heat-generating performance of carbon nanotubes as described in any one of claims 1 to 3 or the carrier for improving the conductive and heat-generating performance of carbon nanotubes obtained by the preparation method as described in any one of claims 4 to 9 in physiotherapy electrodes, wearable heating clothing, wall heating paintings, and glass defrosting films.

Citation Information

Patent Citations

  • Transparent electricity-conducting and heat-conducting flexible film and preparation method thereof

    CN112625286A

  • Carbon nanotube heat dissipation layer and preparation method and application thereof

    CN117820951A

  • Ceramic diaphragm for lithium ion battery and preparation method of ceramic diaphragm

    CN118507992A

  • Method for producing conductive film

    US20150340117A1

Cited By

  • Halogen-free low-dielectric resin composition for copper-clad plate and copper-clad plate

    CN121517859A